The Historic Urban Landscape - Meggyesi, Tamás (4D Journal of Landscape Architecture and Garden Art, 2011)
Following numerous previous documents, recommendations and chartere, through the initiative of the World Heritage Committee, under the aegis of the UNESCO and with the participation of more than 600 professionals of 59 countries, between May 12th and 14th 2005, the so called Vienna Memorandum: „Le Paysage Urbain Historique” has been created, in its English version as „The Historic Urban Landscape”. The text of the Memorandum (its French original) has been translated back then by András Román who entitled it „A történeti városkép kezelése” (Managing the Historic Townscape) in Hungárián. Last year, between November 23rd and 25th, the Observatoire urbaine de Budapest has organized an International conference under this title with the support of the French Institute of Budapest.
Keywords: Urban Landscape; History; UNESCO